Corpus Linguistic Onomastics: A Plea for a Corpus-Based Investigation of Names. (2nd April 2020) - Motschenbacher, Heiko
Abstract : Corpus linguistics is, to date, still an underexplored methodology in onomastics. This article seeks to advance the field through a theoretical discussion of onomastic issues from a corpus linguistic point of view. It presents an overview of the linguistic status, meaning and grammar of proper names in order to highlight aspects that lend themselves to corpus linguistic inquiry. Earlier onomastic research is adduced, to highlight how corpus linguistic methods have substantially improved our understanding of names in language use. While previous onomastic work has often concentrated on the description of names in their own right, without necessarily taking the usage context into account, it is argued that the investigation of the semantics and the grammar of names needs to be complemented by work that draws on usage-based, corpus linguistic evidence. A stronger integration of four types of corpus linguistic analysis (frequency analysis, concordance analysis, collocation analysis, keyword analysis) is suggested for future research.